COED SPORTS AS AN ‘INTEGRATION TOOL’ IN HELLENIC MILITARY HIGHER EDUCATION INSTITUTIONS - Kefi-Chatzichamperi, Evangelia; Irene Kamberidou; Patsantaras, Nikolaos (European Journal of Physical Education and Sport Science (ISSN 2501 – 1235), 2021)
This study focuses on women’s integration in the military through sports, and particularly coed sports in the Hellenic Military Higher Education Institutions: 1) the Hellenic Army Academy, 2) the Hellenic Military Academy of Corps Officers, 3) the Hellenic Military Nursing Academy, 4) the Hellenic Naval Academy, and 5) the Hellenic Air Force Academy. We argue that coed sports (mixed-gender teams) can be used as an integration tool in military institutions, although research on this topic is scarce. Our study begins with a literature review on gender, the military, and sport combining a qualitative and quantitative approach to facilitate a better understanding of how women and men navigate and perceive the meaning of their mixed-gender military sport experience in the Hellenic Military Higher Education Institutions. Initially, twelve Greek women, active officers in the Armed Forces, took part in a series of semi-structured interviews. The twelve women, all high-ranking military officers today—between the ages of 25 to 49—were randomly chosen. Subsequently, a total of 120 active officers of both genders responded to the Greek version of the "Group Environment Questionnaire" (Angelonidis, 1995). From a total of 18 questions, nine were selected to examine gender integration through sport. The main research question is whether sport in the five military higher education academies/schools in Greece contributes to gender integration as perceived and understood by the 120 participants (female and male officers). The findings showed that integration is a process involving non-isolation, meaning acceptance of the gender subject (the officer cadet/military student) regardless of his/her gender into the team, as opposed to his/her exclusion, and as a result the union-unity-acceptance in a sport team of all the subjects (officer cadets of both genders). According to the results of the analysis, there is a statistically significant interaction between the variables 'joint participation of men and women in sports' and the 'integration of women' in the five Hellenic Military Higher Education Institutions. The results of this study indicate that mixed-gender military sport programs serve as a means for gender integration, unity, and cohesion. Other than strengthening physical capacity, fitness and performance, the findings confirm that coed military sport activities could prevent sexism; eliminate or reduce gender harassment, discrimination, and stereotypes; strengthen interpersonal communication/relationships and teamwork; reinforce team and social cohesion, unity, and cooperation skills.   Keywords: Hegemonic masculinity, Sidestreaming, Gender integration, Women, Armed Forces, Military academies, Coed sports, Mixed-gender activities